1982
DOI: 10.1080/00362178285380211
|View full text |Cite
|
Sign up to set email alerts
|

Isolation ofBlastomyces dermatitidisfrom the lungs of a bat,Rhinopoma hardwickei hardwickeigray, in Delhi

Abstract: The isolation of Blastomyces dermatitidis is reported from the lungs of one of 155 insectivorous bats, representing Rhinopoma hardwickei hardwickei Gray, inhabiting the abandoned first floor of a school building in Old Dehli. The identity of the fungus was based on its gross and microscopic cultural morphology including demonstration of its dimorphic character. It was further confirmed by determination of the capacity of the isolate to produce the "A" exo-antigen specific for B. dermatitidis and by verificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

1985
1985
2017
2017

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…[10] Before 1982, nine cases were reported with inadequate documentation. [11] In 1983, Randhawa et al reported the first case of blastomycosis isolated from bronchial aspiration of a female patient from Uttar Pradesh.…”
Section: Discussion Discussionmentioning
confidence: 99%
“…[10] Before 1982, nine cases were reported with inadequate documentation. [11] In 1983, Randhawa et al reported the first case of blastomycosis isolated from bronchial aspiration of a female patient from Uttar Pradesh.…”
Section: Discussion Discussionmentioning
confidence: 99%
“…In this context, our isolation of B. dermatitidis from the liver of R. hardwickei hardwickei, an insectivorous species that had earlier yielded the pathogen from its lungs [10], assumes a special significance. It reinforces the available evidence for the endemic occurrence of B. dermatitidis in India and focuses once again on the possible role of bats as natural hosts or vectors for this pathogen.…”
Section: Discussionmentioning
confidence: 99%
“…B. dermatitidis was not found in any of the 34 samples of bat guano investigated by direct culture or mouse-inoculation technique. The results reinforce the available evidence for the endemic occurrence of B. dermatitidis in India and focus on the possible role of R. hardwickei hardwickei as a natural host or vector for this pathogen.In earlier studies from our laboratory, we reported for the first time the isolation of Blastomyces dermatitidis from a bat, Rhinopoma hardwickei hardwickei Gray, an insectivorous species trapped from the abandoned first floor of a school building in Old Delhi [10], and the first isolation of the pathogen from human clinical material in India [15]. In this communication, we report for the first time the isolation of B.…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…Panja (1925) also diagnosed a case of generalised blastomycosis in scrapings from the cutaneous nodular lesions. Further, the blastomycosis is reported from insectivorous bats (Khan et al 1982), male Mongrel dog (Iyer 1983) and migratory birds (Rawal et al 1988). …”
Section: Blastomycesmentioning
confidence: 96%